2016
DOI: 10.1515/ract-2016-2637
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of U(VI) ions from aqueous solutions by activated carbon prepared from Antep pistachio (Pistacia vera L.) shells

Abstract: AbstractAntep pistachio (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…When Δ H ° < 20 kJ mol –1 , adsorption follows physisorption, while as the Δ H ° > 20 kJ mol –1 , adsorption follows the chemisorption mechanism. The low Δ H ° value of pristine MWNCTs was 11.25 kJ mol –1 , indicating that the adsorption of U­(VI) followed physisorption, and a similar result of 11.33 kJ mol –1 was obtained for U­(VI) onto Antep pistachio shell-derived activated carbon . In contrast, the Δ H ° values of FMTnF-SO 3 H and FMTnF-COOH were 78.2931 and 78.9465 kJ mol –1 , respectively.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…When Δ H ° < 20 kJ mol –1 , adsorption follows physisorption, while as the Δ H ° > 20 kJ mol –1 , adsorption follows the chemisorption mechanism. The low Δ H ° value of pristine MWNCTs was 11.25 kJ mol –1 , indicating that the adsorption of U­(VI) followed physisorption, and a similar result of 11.33 kJ mol –1 was obtained for U­(VI) onto Antep pistachio shell-derived activated carbon . In contrast, the Δ H ° values of FMTnF-SO 3 H and FMTnF-COOH were 78.2931 and 78.9465 kJ mol –1 , respectively.…”
Section: Resultsmentioning
confidence: 62%
“…The low ΔH°value of pristine MWNCTs was 11.25 kJ mol −1 , indicating that the adsorption of U(VI) followed physisorption, and a similar result of 11.33 kJ mol −1 was obtained for U(VI) onto Antep pistachio shell-derived activated carbon. 58 In contrast, the ΔH°values of FMTnF-SO 3 H and FMTnF-COOH were 78.2931 and 78.9465 kJ mol −1 , respectively. It was suggested that U(VI) adsorption might involve the physicochemical interaction, that is, chelation or ion exchange via the functional groups of FMTnF-SO 3 H and FMTnF-COOH.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…18221) as Toprak et al (2012) found in their research employing surrogate wastewater samples. Donat and Erden (2016) used the hull of Antep pistachios to prepare and physicochemically activate carbon at 700 • C in a carbon dioxide-rich atmosphere. The activated carbons formed were found to effectively adsorb physically and remove uranium (VI) from surrogate aqueous solutions.…”
Section: Moussavi and Khosravi 2011mentioning
confidence: 99%
“…A few studies dealt with phenol removal. One work (Donat and Erden, 2016) focused on the (successful) removal of uranium (VI). Nejadshafiee and Reza Islami (2020) treated real waste.…”
Section: Pecan Nutshellmentioning
confidence: 99%